Unpacking gendered discourse in mentorship programs: a critical analysis of the WeAreHERe campaign - Alessandra Colombelli; Luca Falzea; Arianna Montorsi; Greta Temporin (Feminismo/s)
This research paper conducts a Critical Discourse Analysis of the Instagram campaign run by WeAreHERe, a peer-to-peer mentorship program designed for women high school students and first-year university students at Politecnico di Torino. The study scrutinizes 92 posts shared on the WeAreHERe Instagram page during the academic year 2021-2022. The primary goal of the research is, first, to bridge an existing gap in the literature by connecting studies on stereotypes, biases, and mentorship as a constructive means to promote women’s role models with research on gender-based structural oppression. Secondly, this study aims to enhance the WeAreHERe campaign through a comprehensive analysis, ultimately providing insights for shaping future policies about mentorship programs for female students in STEM fields. The analysis showed that most of the posts focus on the individual level rather than on structural oppression and the role models they depict are presented as relatable rather than unique humans. Even when the motivational posts acknowledge the existence of a gender-oppressive structure they seldom mention it clearly, failing to uncover the generative link between this structure of oppression and gender biases and stereotypes. The results show that the literature on stereotypes and biases could be enriched by an approach focused on structural oppression. From these results we developed some guidelines that could help the WeAreHERe campaign – and other similar campaigns that aims at fighting stereotypes about women in the STEM field – to tackle issues of systematic oppression. The use of role models is more effective when it highlights systematic oppression and favours the creation of communities that would help bringing systematic change.